Smokers With Cervix Cancer Have More Uterine Corpus Invasive Disease and an Increased Risk of Recurrence After Treatment With Chemoradiation. Issue 7 (1st September 2014) - Mileshkin, Linda; Paramanathan, Ashvin; Kondalsamy-Chennakesavan, Srinivas; Bernshaw, David; Khaw, Pearly; Narayan, Kailash
Abstract : Background: Smoking is a risk factor for cervix cancer and causes hypoxemia, which promotes tumor infiltration and potentially impacts on treatment outcome. We performed a retrospective study to determine if smokers had an increased risk of uterine corpus infiltration, which is associated with more advanced disease and/or treatment failure after primary chemoradiation. Methods: Results from a prospective database of patients treated with primary chemoradiation for locally advanced cervix cancer with a pretreatment MRI were analyzed. Smoking status was assessed by self-report at presentation. Results: Smoking status was recorded for 346 of the 362 patients with 98 current smokers (28%), 56 ex-smokers (16%), and 192 nonsmokers (55%). Median age was 58 years with ever-smokers having a younger age at diagnosis than nonsmokers. Histologic type, International Federation of Gynecology and Obstetrics stage, tumor volume, and nodal involvement were similar across groups, as were toxicities of treatment. Ever-smokers were more likely to have corpus uterine invasion than nonsmokers. Ever-smokers had more recurrences than nonsmokers, with nonsmokers having a longer median overall survival (50.1 vs 38.7 months, P = 0.004) and relapse-free survival (46.8 vs 28.5 months, P = 0.003). In multifactor analysis, ever-smoking status was a significant predictor of developing corpus invasive disease and of inferior relapse-free and overall survival after treatment. Conclusions: Smokers have a greater risk for developing corpus invasive cervix cancer. Although nonsmokers have an older age at diagnosis, they live longer and have fewer recurrences after a diagnosis of locally advanced carcinoma of the cervix.